Risk profile, antithrombotic treatment and clinical outcomes of patients in Nordic countries with atrial fibrillation - results from the GARFIELD-AF registry - Pope Marita Knudsen; Atar Dan; Svilaas Arne; Hole Torstein; Nielsen Jørn Dalsgaard; Hintze Ulrik; Crisby Milita; Raatikainen Pekka; Airaksinen KE Juhani; Virdone Saverio; Pieper Karen; Kayani Gloria; et al. (TAYLOR & FRANCIS LTD, 2022)
Aims: The objective was to evaluate the clinical characteristics, management and two-year outcomes of patients with newly diagnosed non-valvular atrial fibrillation at risk for stroke in Nordic countries.
Methods: We examined the baseline characteristics, antithrombotic treatment, and two-year clinical outcomes of patients from four Nordic countries.
Results: A total of 52,080 patients were enrolled in the GARFIELD-AF. Out of 29,908 European patients, 2,396 were recruited from Nordic countries. The use of oral anticoagulants, alone or in combination with antiplatelet (AP), was higher in Nordic patients in all CHA(2)DS(2)-VASc categories: 0-1 (72.8% vs 60.3%), 2-3 (78.7% vs 72.9%) and >= 4 (79.2% vs 74.1%). In Nordic patients, NOAC +/- AP was more frequently prescribed (32.0% vs 27.7%) and AP monotherapy was less often prescribed (10.4% vs 18.2%) when compared with Non-Nordic European patients. The rates (per 100 patient years) of all-cause mortality and non-haemorrhagic stroke/systemic embolism (SE) were similar in Nordic and Non-Nordic European patients [3.63 (3.11-4.23) vs 4.08 (3.91-4.26), p value = .147] and [0.98 (0.73-1.32) vs 1.02 (0.93-1.11), p value = .819], while major bleeding was significantly higher [1.66 (1.32-2.09) vs 1.01 (0.93-1.10), p value < .001].
Conclusion: Nordic patients had significantly higher major bleeding than Non-Nordic-European patients. In contrast, rates of all-cause mortality and non-haemorrhagic stroke/SE were comparable.